2018
DOI: 10.21608/ejhc.2018.34043
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Performance Regarding Central Venous Catheters at Neonatal Intensive Care Units

Abstract: A descriptive study was Neonates with central venous catheters constitute a significant group in Neonatal Intensive Care Units. There is no doubt that, adequate care should be applied to them to keep them away from infection. Aim: The study aimed to assess the nurses' performance regarding neonates with central venous catheters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Also, could be attributed to the fact that the young age of nurses may reflect short experience, but it also reflects fresh knowledge and enthusiasm. Mahmoud et al, (2018) [24] , who agreed with this finding as found that the total practices score of more than half of the studied nurses was fair before applying nursing guidelines.…”
Section: Discussionsupporting
confidence: 59%
“…Also, could be attributed to the fact that the young age of nurses may reflect short experience, but it also reflects fresh knowledge and enthusiasm. Mahmoud et al, (2018) [24] , who agreed with this finding as found that the total practices score of more than half of the studied nurses was fair before applying nursing guidelines.…”
Section: Discussionsupporting
confidence: 59%